Patients with paediatric-onset multiple sclerosis are at higher risk of cognitive impairment in adulthood: An Italian collaborative study. (August 2018) - Ruano, Luis; Branco, Mariana; Portaccio, Emilio; Goretti, Benedetta; Niccolai, Claudia; Patti, Francesco; Chisari, Clara; Gallo, Paolo; Grossi, Paola; Ghezzi, Angelo; Roscio, Marco; Mattioli, Flavia; et al.
Background: Patients with paediatric-onset multiple sclerosis (POMS) could be at an increased risk for cognitive impairment (CI), given the potential harmful effects of disease activity in neurodevelopment. However, there is scarce information on their long-term cognitive outcomes. Objective: To compare the prevalence and profile of CI between adults with a history of POMS and those with classic, adult-onset multiple sclerosis (AOMS). Methods: Cognitive performance was assessed through the Brief Repeatable Battery (BRB) and the Stroop Test in consecutive patients referred to six Italian MS centres. CI was defined as impairment in ⩾2 cognitive domains. Results: In all, 119 patients with POMS and 712 with AOMS were included in this analysis. The prevalence of CI was 48.0% in AOMS, 44.5% in POMS; with similar neuropsychological profile between the two groups. However, when adjusting for current age, we found a significantly increased risk for CI (odds ratio (OR) = 1.71; p  = 0.02) and for impairment in information processing speed (OR = 1.86; p  < 0.01) in patients with POMS. A higher Expanded Disability Status Scale (EDSS) was also identified in POMS ( p  = 0.03) compared with AOMS patients. Conclusion: Patients with a history of POMS appear to be at higher risk of physical and cognitive disability than AOMS patients, after correcting for age effects, with particular involvement of information processing speed.